2006
DOI: 10.1093/jac/dkl369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dosing regimen of respirable rifampicin biodegradable microspheres in the treatment of tuberculosis in the guinea pig

Abstract: Aerosolized RPLGA reduced most measures of tuberculosis (TB) infection. These studies are further evidence for the potential of inhaled aerosol therapy for the treatment of TB. However, additional studies are required to elucidate underlying mechanisms of action and optimize this route of drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…and capreomycin particles (pulmonary), with no signs of adverse effects. Wet lung and spleen weights for treated animals were employed as an indication of the degree of inflammation of each organ (6,7,9,13,18,24). Figure 3 shows the organ weights corrected by body weight at the time of necropsy.…”
Section: Resultsmentioning
confidence: 99%
“…and capreomycin particles (pulmonary), with no signs of adverse effects. Wet lung and spleen weights for treated animals were employed as an indication of the degree of inflammation of each organ (6,7,9,13,18,24). Figure 3 shows the organ weights corrected by body weight at the time of necropsy.…”
Section: Resultsmentioning
confidence: 99%
“…One such treatment is a drug delivery system that sustains release of drugs and targets the primary site of action, the lungs. Rifampicin and other antitubercular drugs have been investigated in polymeric particle form for inhalation as both microparticles (34)(35)(36)(37) and nanoparticles (38)(39)(40)(41). These studies have shown that treatment with nebulized or insufflated particles containing antibiotics is effective in decreasing bacterial counts in infected animals with reduced doses.…”
Section: Discussionmentioning
confidence: 99%
“…Aerosols of rifampicin solutions and suspensions of biodegradable particles have been delivered by this chamber for the treatment of tuberculosis [110,98].…”
Section: Passive Inhalationmentioning
confidence: 99%